Machine Learning-Based Predictive Maintenance at Smart Ports Using IoT Sensor Data - Aslam, Sheraz; Navarro, Alejandro; Aristotelous, Andreas; Garro Crevillen, Eduardo; Martinez-Romero, Alvaro; Martínez-Ceballos, Álvaro; Cassera, Alessandro; Orphanides, Kyriacos; Herodotou, Herodotos; Michaelides, Michalis P. (My University, 2025)
Maritime transportation plays a critical role in global containerized cargo logistics, with seaports serving as key nodes in this system. Ports are responsible for container loading and unloading, along with inspection, storage, and timely delivery to the destination, all of which heavily depend on the performance of the container handling equipment (CHE). Inefficient maintenance strategies and unplanned maintenance of the port equipment can lead to operational disruptions, including unexpected delays and long waiting times in the supply chain. Therefore, the maritime industry must adopt intelligent maintenance strategies at the port to optimize operational efficiency and resource utilization. Towards this end, this study presents a machine learning (ML)-based approach for predicting faults in CHE to improve equipment reliability and overall port performance. Firstly, a statistical model was developed to check the status and health of the hydraulic system, as it is crucial for the operation of the machines. Then, several ML models were developed, including artificial neural networks (ANNs), decision trees (DTs), random forest (RF), Extreme Gradient Boosting (XGBoost), and Gaussian Naive Bayes (GNB) to predict inverter over-temperature faults due to fan failures, clogged filters, and other related issues. From the tested models, the ANNs achieved the highest performance in predicting the specific faults with a 98.7% accuracy and 98.0% F1-score.
Keywords: IoT; machine learning; predictive maintenance; smart ports